IGNACIO ASSIS SILVA AND LITERARY STUDIES - Leonel, Maria Célia (Laboratório Editorial FCL-UNESP, 2011)
This paper aims to honor the semiotician Ignacio Assis Silva printed by the intensity in all his activities, emphasizing mainly on the accuracy insightful essays, which made him not only one of the most important promoters of semiotics greimasian in Brazil, but one of those responsible for its development. It should be noted also that he served with dedication in the Postgraduate Program in Literary Studies FCL/Araraquara UNESP, including efforts since its founding. The program owes much to him and others of FCL semioticians for the healthy integration between programs, Linguistics/Portuguese Language and Literary Studies. The latter was even initially, a literature program focusing on semiotics greimasian. Join together with all his persistent interest in building a "theory of language", which deeply and tenaciously pursued in their classes and in their texts and can be detected in Figurativização e metamorfose: o mito de Narciso (1995).